Gambaran Pengetahuan Golongan Darah Untuk Memenuhi Kebutuhan Transfusi Darah - Dewi Nur Anggraeni (Poltekkes Kemenkes Padang, 2022)
Blood type is a genetic substance that is inherited. Each individual has the characteristics of blood groups A, B, AB and O, until now known blood types are accompanied the information Rhesus (Rh) + and Rhesus (Rh) -. Several cases that often occur in Wedomartani Village are blood loss from community members that cannot be resolved and the community's lack of knowledge about blood types when blood transfusion activities will be carried out. The purpose of this study was to determine the description of blood type knowledge to needs of blood transfusions. The population study was 35 families, and the sample data were 100 people. The data collection method was by distributing questionnaires containing several questions related to blood type knowledge, data analysis using the univariate method. The results obtained are as many as 100 respondents have sufficient knowledge about the importance of blood type for the need for blood transfusion by 48%. The conclusion is the description of blood type knowledge to needs of blood transfusions from the people of Wedomartani Village,in the sufficient category, this category is influenced by educational background, gender, age, and occupation of the community. Suggestions from the research are that there is a need for follow-up in the form of socializing activities about meeting the need for blood transfusions, along with checking blood types in Wedomartani Village.